Effect of high hydrostatic pressure treatments on physicochemical properties, microbial quality and sensory attributes of beef carpaccio - Szerman, Natalia (2011)
11th International Congress on Engineering and Food (ICEF11), Atenas, Grecia, 22-26 May 2011